The Impact of Utilization The Solar-Panels With a Cooling-Water System as a Source of Micro-Power Generation - Setyono, Gatot; Kholili, Navik; Rakhmadanu, Yanuariza (Infotekmesin, 2022)
The optimal approach to enhance solar panel efficiency and decrease the degradation rate is to lower the temperature range of the surface area. It will be applied by allowing the panels/modules to be cooled and lessening the heat stored in the solar cells through an operation. In the research using experimental methods, the solar panels used have a capacity of 100 WP as a source of micro-power generation, the angle of inclination of the panels is adjusted with variations of 150, 200, and 250. The cooling system uses water, the process of draining water using a submersible pump mounted on a reservoir Water flows to all surfaces of the solar panel and circulates continuously when operating. The experimental outcomes show that the cooling process utilizing water has reduced the temperature operating of the solar panels. The decrease in average temperature occurred in all variations of 23%. The cooling process significantly affects the output power and operational efficiency; circulating cooling can increase the scale of incidents solar radiation on the solar panel due to the refractive effect of the water layer and keep the surface of the solar panel clean from dirt and dust. Output power and operational efficiency have increased in almost all variations in the angle of the solar panel tilt (150, 200, and 250), output power has increased by an average of 22%, and efficiency has increased by on average of 2%